Strategi Guru PAI dalam Internalisasi Core Values Madrasah - Muchammad Syafii; Joko Subandono (TSAQOFAH, 2026)
The internalization of madrasah core values has become an important issue in strengthening character education, particularly when Islamic Religious Education (PAI) teachers are required to align institutional values with national curriculum policies that are implemented simultaneously. This study aims to describe PAI teachers’ strategies in internalizing the five core values of MALISKA B’RANI MAJU, namely Happy, Friendly, Disciplined, Independent, and Honest, at Madrasah Aliyah Al-Islam Jamsaren Surakarta, and to map their synergy with Panca Cinta in the Love-Based Curriculum (KBC) based on Decree of the Director General of Islamic Education Number 6077 of 2025 and the eight dimensions of the graduate profile in the Deep Learning approach in accordance with Regulation of the Minister of Primary and Secondary Education Number 13 of 2025. This study used a library research method with an analytical-conceptual approach through the review of regulations, character education theory, and recent empirical literature. The results of the review show a very high level of alignment among the core values of MALISKA B’RANI MAJU, the pillars of Panca Cinta in KBC, and the dimensions of the Deep Learning graduate profile because all three are grounded in universal Islamic values. The six main internalization strategies identified include uswah hasanah, systematic habituation, mau‘izhah hasanah, meaningful learning, reflection-based mindful learning, and collaborative project-based joyful learning. This study affirms that the effectiveness of core value development in madrasahs depends greatly on the consistency of PAI teachers’ exemplary conduct and their ability to integrate KBC with the Deep Learning approach synergistically. The implications of this study encourage madrasahs to formalize a synergy map among madrasah core values, Panca Cinta in KBC, and the Deep Learning graduate profile in the operational curriculum document as a basis for strengthening Islamic value-based character education.